Association between Sources of PM2.5 and Cardiopulmonary Mortality: A Time-series Analysis in Taipei Metropolitan Area - Tuan-Hung Ngo; Chih-Da Wu; Kai-Hsien Chi; Wen-Chi Pan (Aerosol and Air Quality Research)
Abstract Researches about the association between PM2.5 and health impact are mainly focused on mass concentrations of PM2.5, but little is known how sources of PM2.5 affect disease risks. In this study, we utilized data from air pollution monitoring stations in the Taipei Metropolitan area (2006–2016) for source apportionment analysis and then used the concentration of PM2.5 from different sources for health risk study. Cluster analysis and bivariate polar plot for PM2.5 and weather data from five monitoring stations were used for source apportionment. A stratified time-series analysis was performed to evaluate the association between sources of PM2.5 and the risk of mortality (i.e., cardiovascular diseases [CVD] and respiratory diseases [RD]). We found 74.1 ± 23.4% of PM2.5 at Taipei was traffic originated whereas stationary sources contributed 23.5 ± 19.4%. Stacked-PM2.5 was associated with higher mortality risk than traffic-PM2.5 (RR = 1.006 vs. 1.004 for CVD mortality; RR = 1.020 vs. 1.008 for RD mortality). At places with unmixed sources of air pollution, the mass concentration of PM2.5 can still serve as an indicator of health risk caused by PM2.5.